Just a job? : communication, ethics, and professional life - Cheney, George (New York ; Oxford : Oxford University Press, 2010)
The concept of 'professionalism' has gained everyday resonance in the 21st century, especially given recent corporate scandals. However, George Cheney argues, as much as it may be discussed professionalism has lost much of its broader social and community-related implications.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Occupations; Professional ethics; Success